An investigation of e-commerce adoption inhibitors in the Tourism industry: A Zimbabwe National Parks Perspective - Chivandi, Abigail; Sibanda, Fortune (Africa Journals, 2021)
The purpose of the study was to investigate e-commerce adoption inhibitors within the Tourism industry in the Zimbabwe National Parks as one of the key benefits that comes with proper and effective use of e-commerce, improved availability, processing and dissemination of information. Information can be distributed, shared with various business partners across the board efficiently. The study aimed at enabling E-commerce information to be shared, accessed and disseminated at a minimum time and cost reduction in the Zimbabwe National Parks. As information accessing and processing is now done electronically, there is reduction in the degree of inefficiency caused by human error. With the ready availability of contemporary information, various business entities can make conversant decisions that will be critical to their development and ultimately sustainability. The research was undertaken by examining Zimbabwe National Parks and their sub-units. A survey, via a pretested questionnaire based on a Likert scale and in-depth interviews was used to gather data and compute it. The results indicated that the companies distance and geographical constraints have limited or hindered the development and growth of many business prospects but e-commerce has cut across the geographic boundaries of the various countries. Business networks are now possible in Zimbabwe National Parks, for vertical integration, supply chain management, and business links reduce routine transactional time and costs.